2008
DOI: 10.2337/dc07-1158
|View full text |Cite
|
Sign up to set email alerts
|

The PTPN22 1858T Gene Variant in Type 1 Diabetes Is Associated With Reduced Residual β-Cell Function and Worse Metabolic Control

Abstract: FOR THE IMMUNOTHERAPY DIABETES (IMDIAB) GROUP 3OBJECTIVE -Evidence has been reported for a new susceptible locus for type 1 diabetes, the protein tyrosine phosphatase nonreceptor type 2 (PTPN22), which encodes a lymphoidspecific phosphatase. The aim of the study was to evaluate the influence of the C1858T variant of the PTPN22 gene on ␤-cell function as measured by C-peptide levels from time of disease diagnosis through 12 months follow-up in a prospective series of 120 consecutive type 1 diabetic subjects.RES… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
30
1
4

Year Published

2009
2009
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 18 publications
4
30
1
4
Order By: Relevance
“…Associations between genetic factors such as HLA [37,38], PTNP22 gene [26], and C-peptide levels in T1DM patients have already been described. Petrone et al [37] reported that individuals with high-risk HLA DRB1-DQB1 genotypes had lower C-peptide levels at diagnosis.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Associations between genetic factors such as HLA [37,38], PTNP22 gene [26], and C-peptide levels in T1DM patients have already been described. Petrone et al [37] reported that individuals with high-risk HLA DRB1-DQB1 genotypes had lower C-peptide levels at diagnosis.…”
Section: Discussionmentioning
confidence: 91%
“…Recently the PTNP22 1858T gene variant was found to be associated with reduced ␤-cell function in T1DM patients followed by 12 months after diagnosis. The authors commented that this could be due to a particular insulin therapy approach or to a more aggressive autoimmune process, as this gene encodes a lymphoid tyrosine phosphatase that alter T-regulatory cell function [26]. This was the first study that tried to evaluate the relationship between VDR polymorphisms and residual pancreatic ␤-cell function.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Наибольший вклад среди остальных вносят: гены инсулина, гены CTLA-4, PTPN-22, выполняющие ключевую роль в координации иммун-ного ответа и др. [5] (CTLA-4 играет основную роль в механизме ответа Т-клеток на презентацию антигена, кодирует ко-стимули-рующую молекулу, экспресс ирующуюся на поверхности активи-зированного Т-лимфоцита. PTPN-22 кодирует тирозиновую фосфатазу Т-лимфоцитов, которая является внутриклеточным белком, экспрессия которой специфична для клеток иммунной системы и является одним из «негативных регуляторов» иммун-ной системы).…”
Section: с сunclassified
“…Таким образом, среди заболев-ших в 82% случаях определялись гаплотипы высокого риска (ге-нотип DQ2/DQ8 встречался в 18,2%, генотипы DQ2/Х и DQ8/Х -в 63,6% случаев) и только 18,2% заболевших не имели предраспо-лагающих гаплотипов. Полученные данные еще раз подтвердили, что наличие предрасполагающих гаплотипов важно для прогно-зирования заболевания, однако и отсутствие этих гаплотипов не исключает в небольшом проценте развития СД, что может быть обусловлено влиянием других предрасполагающих генов [5]. Таким образом, в наших исследованиях генотипы HLA-DQ2/DQ8; DQ2/X; DQ8/X прогнозируют примерно с 8-процентной веро-ятностью риск развития СД1 на протяжении 11-летнего периода.…”
Section: результаты и их обсуждениеunclassified